RATAPAN KESEDIHAN DALAM LAGU YA QUDS KARYA NAWAL AZ-ZAGHBI BERDASARKAN PERSPEKTIF GEORGE LUCASS - Lu’lu’il Karimah; Abdul Muntaqim Al Anshory; Dien Nur Chotimah (Prosiding Konferensi Nasional Bahasa Arab, 2017)
Abstrak: A song is one of the literary works that became a part of social life representation. This research discus about “the sadness” in the song titled Ya Quds by Nawal Az-Zaghbi with sociological approach of literary work. This song tells about expressions of sadness occurred in Yarussalem society because of unendless war that caused many damages. The theme of the song is about nationalism in idealism and culture in sacrifice. The research question in this research is how the lament of sadness is contained in the song Ya Quds by Nawal az-Zaghbi according to George Lucass. This research uses descriptive qualitative method which explains a research by words with explanation that defines how the condition is. The purpose of this research is to describe how the threnodies of sadness occurred in Yarussalem society, either the sadness of decay or the sadness of pain. The data in this research is known by sociological theory of literary work which assumes that literary work is a result of the real condition of society and representation of their live. Depends on this research, it is concluded that expressions occurred in the song Ya Quds is what happened in Yarussalem society. Yarussalem society who are sad because of lossing their family and missing to the peaceful of their country. Kata Kunci : The Sadness, Song of Ya Quds, George Lucas